Hypercholesterolemia promotes autoantibody production and a lupus‐like pathology via decreased DNase‐mediated clearance of DNA. Issue 20 (13th September 2022) - Dhawan, Umesh Kumar; Margraf, Andreas; Lech, Maciej; Subramanian, Manikandan
Abstract: Hypercholesterolemia exacerbates autoimmune response and accelerates the progression of several autoimmune disorders, but the mechanistic basis is not well understood. We recently demonstrated that hypercholesterolemia is associated with increased serum extracellular DNA levels secondary to a defect in DNase‐mediated clearance of DNA. In this study, we tested whether the impaired DNase response plays a causal role in enhancing anti‐nuclear antibody levels and renal immune complex deposition in an Apoe −/− mouse model of hypercholesterolemia. We demonstrate that hypercholesterolemic mice have enhanced anti‐ds‐DNA and anti‐nucleosome antibody levels which is associated with increased immune complex deposition in the renal glomerulus. Importantly, treatment with DNase1 led to a decrease in both the autoantibody levels as well as renal pathology. Additionally, we show that humans with hypercholesterolemia have decreased systemic DNase activity and increased anti‐nuclear antibodies. In this context, our data suggest that recombinant DNase1 may be an attractive therapeutic strategy to lower autoimmune response and disease progression in patients with autoimmune disorders associated with concomitant hypercholesterolemia.